Thermo-Reversible Persistent Phosphorescence Modulation Reveals the Large Contribution Made by Rigidity to the Suppression of Endothermic Intermolecular Triplet Quenching - Kusama, Tomoya; Hirata, Shuzo (Frontiers in Chemistry, 2021)
The suppression of thermally driven triplet deactivation is crucial for efficient persistent room-temperature phosphorescence (pRTP). However, the mechanism by which triplet deactivation occurs in metal-free molecular solids at room temperature (RT) remains unclear. Herein, we report a large pRTP intensity change in a molecular guest that depended on the reversible amorphous–crystal phase change in the molecular host, and we confirm the large contribution made by the rigidity of the host in suppressing intermolecular triplet quenching in the guest. (S)-(−)-2,2′-Bis(diphenylphosphino)-1,1′-binaphthyl ((S)-BINAP) was doped as a guest into a highly purified (S)-bis(diphenylphosphino)-5,5′,6,6′,7,7′,8,8′-octahydro-1,1′-binaphthyl ((S)-H8-BINAP) host. It was possible to reversibly form the amorphous and crystalline states of the solid by cooling to RT from various temperatures. The RTP yield (Φp) originating from the (S)-BINAP was 6.7% in the crystalline state of the (S)-H8-BINAP host, whereas it decreased to 0.31% in the amorphous state. Arrhenius plots showing the rate of nonradiative deactivation from the lowest triplet excited state (T1) of the amorphous and crystalline solids indicated that the large difference in Φp between the crystalline and amorphous states was mostly due to the discrepancy in the magnitude of quenching of intermolecular triplet energy transfer from the (S)-BINAP guest to the (S)-H8-BINAP host. Controlled analyses of the T1 energy of the guest and host, and of the reorganization energy of the intermolecular triplet energy transfer from the guest to the host, confirmed that the large difference in intermolecular triplet quenching was due to the discrepancy in the magnitude of the diffusion constant of the (S)-H8-BINAP host between its amorphous and crystalline states. Quantification of both the T1 energy and the diffusion constant of molecules used in solid materials is crucial for a meaningful discussion of the intermolecular triplet deactivation of various metal-free solid materials.